Role of B-type natriuretic peptide in diagnosis of coronary artery disease - Boyraz, Bedrettin; Mutluer, Ferit Onur; Çakır, Hakan; Topal, Dursun; Demir, Mehmet; Er, Fahri; Peker, Tezcan; Yılmaz, Mustafa; Akgümüş, Alkame; Tenekecioğlu, Erhan (The European Research Journal, 2019)
Objectives: B-type natriuretic peptide (BNP) has been extensively studied as a biomarker in heart failure. There is clear benefit of BNP in diagnosis and risk stratification of several cardiac diseases including acute coronary syndromes. Our aim was to evaluate diagnostic role of changes in BNP levels with exercise in coronary artery disease (CAD).Methods: Fifty-one patients underwent exercise stress testing (EST) for suspected CAD and consequently underwent coronary angiography (CA) were prospectively enrolled. Patients with and without at least one significant diameter stenosis in major epicardial arteries (CA+ and CA-) versus patients with and without evidence of myocardial ischemia during exercise stress testing (EST+ and EST-) were classified into 4 groups, respectively (Group 1, CA+/EST+; group 2, CA+/EST-; group 3, CA-/EST+; and group 4, CA-/EST-). All patients underwent EST. Blood was drawn from patients for determination of BNP levels 10 minutes prior to, 10 minutes after and 4 hours after EST.Results: EST parameters other than the parameters signifying myocardial ischemia didn’t differ significantly among groups (p > 0.05). Pre-exercise, post-exercise and 4h-post exercise BNP values were significantly higher in group 1 and group 2 compared to group 3 and group 4 (p < 0.05 for all comparisons between the groups for pre-exercise, post-exercise and 4h-post exercise BNP). Exercise-induced increases in BNP were higher in group 1 and group 2. Patients with significant CAD involving LAD demonstrated higher basal and exercise-induced BNP as well as BNP increases, irrespective of the EST result. Conclusions: Basal, maximal-exercise and post exercise BNP values predicted CAD, as well as CAD involving LAD irrespective of ischemic changes in EST. Our results point out potential role of BNP as an adjunct to EST in diagnosis and management of CAD.